Recovering resources from wastewater screenings through Anaerobic Digestion and Phosphorus Precipitation - Newati Wid; Nigel Horan (2017)
Background: The potential of a material that has received little attention, namely wastewater screenings produced during wastewater treatment, was examined for recovering valuable products, in the form of methane and phosphorus, in order to turn this waste into useful resources. Anaerobic digestion was performed to recover biogas that has sustainable energy in the form of methane as its main component. The nutrient released in the residual digested liquor can then be precipitated as struvite, which allows its recovery as phosphorus, which is reported is depleting.